Impact of Development on Regional Pollution - Faradiba Faradiba (PT Mattawang Mediatama Solution, 2024)
Economic development is one of the government's priority programs. However, in the middle of the development process, it turns out that evolution harms the environment. The environmental impact that usually occurs is pollution. This study aims to determine the role of development on pollution. This study uses a composite index calculation of the presence of pollution from each village/kelurahan area in Indonesia. Multiple linear regression was used to determine the effect of GRDP on the pollution composition index. The results of this study indicate that GRDP has a positive and significant impact on regional pollution. Special efforts are needed from the government to tackle pollution problems due to development activities. The government can issue regulations so that companies, as polluters' main polluters, can pay more attention to the environmental impacts they cause.